Anmeldelser - Redaktionen, - (Geografisk Tidsskrift, 1969)
Litteraturanmeldelser: FYSISK GEOGRAFI M. M. Hart: The Earth's Crust and Upper Mantle (K. H.) ......................... 225 Minato: Pacific Geology IK. H.) ............................................ 226 Paterson: The Physics of Glaciers (B. F.) ................................... 226 Petterssen: Introduction to Meteorology (K. M. J.) ......................... 226 Acta Cartographica (N. N.) ................................................... 224 KARTOGRAFI M. M. Acta Cartographica (N. N.) ................................................... 224 KULTUR- OG ERHVERVSGEOGRAFI Harris: The Rise of Anthropological Theory (C. G. F.) .................... 229 Breslen: Environments of Man (R. H. J.) .................................. 231 Johnson: The Nature of Nomadism (C. G. F.) .............................. 232 Manshard: Agrargeographie der Tropen (C. G. F.) ......................... 233 EUROPA OG SOVJETUNIONEN Gutkind: Urban Development in Southern Europe (N. N.) .................. 231 FREMMEDE VERDENSDELE Niebuhr: Reisebeschreibung nach Arabien (N. N.) ......................... 224 Fischer: Afghanistan (N. N.) ................................................. 235 Dempster: Japan Advances (S. C.) .......................................... 236 Mensching: Tunesien (Aa. Aa.) .............................................. 232 Peterec: Dakar and West African Economic Development (C. G. F.) ...... 232 Carcon: Materials for West African History in French Archives (C. G. F.). . 233 Mühlenpfordt: Schilderung der Republik Mexico (N. N.) .................... 235 Clark: Acadia (N. N.) ......................................................... 225 Meyers Kontinente und Meere: Mittel- und Südamerika (Aa. Aa.) ........ 234 Osborne: Australia, New Zealand, South Pacific (S. C.) .................... 236 Gale & Lawton: Settlement & Encounter (S. C.) ............................ 236 Yehoshua Ben-Arieh: The Changing Landscape of the Central Jordan Valley (S.I.) ....................................................................... 238 Alfred Hettner: Reisen in den Columbianischen Anden (N.N.) ............. 238 POLAREGNENE Bushnell & Ragle: Icefield Ranges Research Project (B. F.) ................ 227 Furrer: Subnivalen Formenschatz in Ostspitzbergen und in den Schweizer Alpen (B. F.) .............................................................. 227 Osburn & Wright : Arctic and Alpine Environments (B. F.) ................ 227 Dunbar: Ecological Development in Polar Regions (B. F.) ................ 228 Kristoffersen: Jæger og fangstmand (B. F.) ................................. 228 Nelson: Hunters of the Northern Ice (B. F.) ................................ 228 Ray: Graphic Arts of the Alaskan Eskimo (B. F.) ......................... 229 LÆREBØGER M. M. Stanford & Moran: Geography (R. H. J.) ..................................... 237 BØGER INDGÅET TIL REDAKTIONEN ................ 239